Touchless interaction in surgical settings - Carrell, Tom; Mentis, Helena; Penney, Graeme; Criminisi, Antonio; O'Hara, Kenton; Sellen, Abigail; Rouncefield, Mark; Dastur, Neville; Varnavas; Corish, Bob (Communications of the ACM, 2014)
With advances in medical imaging technologies in recent decades, we have seen their widespread adoption in the context of surgical procedures. While surgeons are increasingly reliant on these technologies, their ability to interact with them during surgery is restricted by traditional touch-based input mechanisms due to the need to maintain sterility. In response to the need to provide surgeons with control over medical images while maintaining sterility we are seeing a number of research initiatives exploring ways of interacting with these imaging technologies without touching, in particular through the use of gesture and voice control. Given the growing interest in the area, it is an opportune time to take a reflective look at the corpus of initiatives to highlight key lessons learned as well as some of the issues and challenges relevant to the development of these systems. As well as the key technical challenges to be faced, we also highlight how key socio-technical concerns play an important role in the ways we approach the design of these systems and illustrate this through some of our own development experiences in this area. In light of discussion we offer some directions for the future progress of the field.